Las actividades físico-recreativas en los adultos mayores y su relación con el estrés durante el confinamiento por el covid-19 - Ortiz Chico, Andrea Stefanía (2022)
The present research analyzes the context of a group considered vulnerable in a confinement environment with high stress levels, faced by a global threat in recent months by the Coronavirus 2019 (COVID-19) disease, caused by SARS-CoV-2. The objective was to determine the influence of physical recreational activities in older adults on stress levels during confinement by Covid-19. The research is presented with a qualitative character of exploratory transversal type, with the instruments were applied individually to the older adults of the Foundation Su Cambio por el Cambio and the Gerontological Center of the San Simón Parish. The instruments used in the research were the Physical Activity Scale for the Elderly (PASE) for the independent variable and the Zung Depression Scale for the independent variable. It is determined that 37 older adult subjects of the study population representing 92.5% are slightly depressed. It is determined that the practice of Physical-Recreational Activities decreases the levels of stress in older adults during the confinement of the Covid-19